2019–2020 Florida Citrus Production Guide: Interpreting PPE Statements on Pesticide Labels - Frederick M. Fishel (EDIS, 2019)
This 3-page fact sheet is part of the 2019–2020 Florida Citrus Production Guide. This document helps you understand the revised PPE statements now part of labels on pesticide products used on farms, forests, nurseries, and greenhouses. Written by Frederick M. Fishel and published by the Agronomy Department, March 2019.